The Determinants of Wealth and Gender Inequity in Cognitive Skills in Latin America - Macdonald, Kevin; Barrera, Felipe; Guaqueta, Juliana; Patrinos, Harry Anthony; Porta, Emilio (World Bank, Washington, DC, 2014)
Wealth and gender inequity in the accumulation of cognitive skills is measured as the association between subject competency and wealth and gender using the OECD s Programme for International Student Assessment. Wealth inequity is found to occur not through disparate household characteristics but rather through disparate school characteristics; little evidence is found of an association between wealth and competency within schools. Weak evidence is found of wealth mitigating gender differences through school characteristics. These findings suggest that wealth inequity in the accumulation of cognitive skills is almost exclusively associated with disparate school characteristics and that disparate school characteristics may play a role in accentuating gender inequity.